Influence of patient position and other inherent factors on image quality in two different cone beam computed tomography (CBCT) devices. (2017) - Lindfors, Ninita; Lund, Henrik; Johansson, Hans; Ekestubbe, Annika
Highlights: Patient head position can affect the image quality in CBCT-examinations. CNR values can be used to evaluate image quality. Inherent factors influence effective dose variations between CBCT-devices. Abstract: Objectives: The aim of this in vitro study was to evaluate how a deviation from the horizontal plane, affects the image quality in two different CBCT-devices. Methods: A phantom head SK150 (RANDO, The Phantom Laboratory, Salem, NY, USA) was examined in two CBCT-units: Accuitomo 80 and Veraviewepocs 3D R100 (J. Morita Mfg. Corp. Kyoto, Japan). The phantom head was placed with the hard palate parallel to the horizontal plane and tilted 20 ° backwards. Exposures were performed with different field of views (FOVs), voxel sizes, slice thicknesses and exposure settings. Effective dose was calculated using PCXMC 2.0 (STUK, Helsinki, Finland). Image quality was assessed using contrast-to-noise-ratio (CNR). Region of interest (ROI) was set at three different levels of the mandibular bone and soft tissue, uni- and bilaterally in small and large FOVs, respectively. CNR values were calculated by CT-value and standard deviation for each ROI. Factor analysis was used to analyze the material. Results: Tilting the phantom head backwards rendered significantly higher mean CNR values regardless of FOV. The effective dose was lower in small than in large FOVs and varied to a larger extent between CBCT-devices in large FOVs. Conclusions: Head position can affect the image quality. Tilting the head backward improved image quality in the mandibular region. However, if influenced by other variables e.g. motion artifacts in a clinical situation, remains to be further investigated. Advances in knowledge: Image quality assessed using CNR values to investigate the influence of different patient positions and FOVs.